Variation in resource allocation in urgent and emergency Care Systems in Ireland - Steve Thomas; Conor Foley; Bridget Kane; Bridget M. Johnston; Brenda Lynch; Susan Smith; Orla Healy; Elsa Droog; John Browne (BMC, 2019)
Abstract Background A key challenge for most systems is how to provide effective access to urgent and emergency care across rural and urban populations. Tensions about the placement and scope of hospital emergency services are longstanding in Irish political life and there has been recent reform to centralise hospital services in some regions. The focus of this paper is a system approach to examine the geographic variation in resourcing and utilisation of such care across GP practices, out-of-hours care, ambulance services, Emergency Departments and Local Injury Units in Ireland. Methods We used a cross-sectional study design to evaluate variation in resource allocation by aggregating geographic funding to various elements of the urgent and emergency care system and assessing patterns in hospital resource utilisation across the population. Expenditure, staffing, access and activity data were gathered from government sources, individual facilities and service providers, health professional bodies, private firms and central statistics. Data on costs and activity in 2014 are collated and presented at both county and regional levels. Analyses focus on resources spent on urgent and emergency care across geographic areas, the role of population concentration in allocation, the relationship between pre-hospital spending and in-hospital spending, and the utilisation of hospital-based emergency care resources by residents of each county. Results An array of funding mechanisms exists, resulting in a fragmented approach to the resourcing of urgent and emergency care. There are large differences in spending per capita at the county-level, ranging from between €50 and €200 per capita; however, these are less pronounced regionally. Distribution of hospital emergency care resources is highly skewed to the North East of the country, and away from the recently reconfigured South and Mid-West regions. Conclusions This analysis advances the traditional approach of evaluating individual services or hospital resourcing. There are notable differences in utilisation of hospital-based emergency care resources at the regional level, indicating that populations within those regions which have been reconfigured have lower utilisation of hospital resources. There is a clear case for more integration in decision-making around funding and consideration of key principles, such as equity, to guide that process.